NON-NATIVE ARABIC LANGUAGE TEACHER: LOW TEACHER’S PROFESSIONAL COMPETENCE LOW QUALITY OUTCOMES? - Anwar Sanusi; Sofyan Sauri; Yayan Nurbayan (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2020)
This study aimed at investigating the problems of Arabic teachers’ professional competence in improving the quality of the graduates at MA Al-Musdariyah 2 Cimahi. Phenomenology, scientific approach, and a formal juridical approach were used as the method in this study. This study belonged to a case study. The result of this study showed that the main problems related to the teacher’s professional competence in teaching and learning Arabic were an unsuitable academic qualification, the lack of teachers’ welfare, teachers’ discipline and awareness, tutoring, and training. The implication of this study indicated that teachers’ professional competence to improve the quality of the graduates had been implemented. However, the implementation of teachers’ professional competence was considered less than optimal. It influenced the quality of the graduates. In other words, the objectives of teaching and learning activities were not achieved. Therefore, in this case, teachers as the most important factor in teaching and learning processes should improve their competences as a manifestation to improve the quality of the graduates.